O11 Chemsex and the city: sexualised substance use in gay bisexual and other men who have sex with men. (18th May 2015) - Lee, Ming; Hegazi, Aseel; Barbour, Alison; Nathan, Bavithra; Green, Simon; Simms, Richard; Pakianathan, Mark
Abstract : Background/introduction: Sexualised substance use (chemsex) is an emergent phenomenon amongst some gay, bisexual and other men who have sex with men (GBMSM). Aim(s)/objectives: To describe patterns of chemsex and clinical characteristics of GBMSM attending two London sexual health clinics. Methods: Retrospective case-notes review. Data on demographics, chemsex practices, sexual behaviour, STI diagnoses and HIV status extracted from a new holistic standardised profoma used in GBMSM clinics June to December 2014. Results: 27% (n = 127) of 531 cases disclosed drug use. 59% (n = 73/124) reported chemsex, 13% (n = 15/116) injected. Drugs: Mephedrone (n = 48), GHB/GBL (n = 38), Crystal Meth (n = 28) and Cocaine (n = 8). 1/3 disclosed > one chemsex session/month. Chemsex was significantly associated with the risk taking behaviours transactional sex, group sex, fisting, sharing sex toys, HIV and hepatitis sero-discordancy (p < 0.05), more reported sexual partners (median 3 vs. 2 in past 3 months; P < 0.0001) and HIV positivity (35% vs 7% p < 0.0001). STIs were diagnosed more frequently in chemsex participants; Gonorrhoea (39% vs. 6% p < 0.0001), Chlamydia (11% vs. 4% p = 0.05), Hepatitis C (5% vs 0.3% p = 0.03) and PEPSE was more frequently prescribed (14% vs. 2% p = 0.001). 42% of patients perceived chemsex to have had an adverse consequences on their physical/ mental health or career. Discussion/conclusion: The majority of GBMSM reporting chemsex were HIV negative and many perceived negative consequences from chemsex. It was also significantly associated with risk taking behaviours, STIs, hepatitis C and being HIV positive. A holistic assessment of GBMSM enables the identification of opportunities for targeted prevention, health promotion and wellbeing interventions.